A simplified universal approach to COH protocol for IVF: ultrashort flare GnRH-agonist/GnRH-antagonist protocol with tailored mode and timing of final follicular maturation. Issue 1 (December 2015) - Orvieto, Raoul
Abstract Recently, several new promising modifications have been introduced to clinical practice that may simplify and optimize IVF outcome. In the present opinion paper we present a simplified approach to controlled ovarian hyperstimulation protocol (COH), which combines the benefits of the ultrashort flare GnRH agonist/GnRH antagonist protocol and the personalized tailored mode and timing of ovulation triggering, aiming to improve IVF outcome while eliminating of severe OHSS. In patients at risk to develop severe ovarian hyperstimulation syndrome (OHSS), GnRH agonist (GnRHa) trigger if offered for final follicular maturation. While in those achieving ≥20 oocytes, the freeze all policy with the subsequent frozen-thawed embryo transfers (ET) is recommended, in those where less than 20 oocytes are retrieved, patients are re-evaluated 3 days after oocyte retrieval (day of ET) for signs of early moderate OHSS. If no early signs of OHSS developed, one embryo was transferred, and the patients are instructed to inject 1500 IU of HCG. In cases where signs of early moderate OHSS appear, the freeze all policy is recommended. In Patients not at risk to develop severe OHSS- three different modes of concomitant administration of both GnRHa and a standard bolus of hCG (5000–10, 000 units) prior to oocyte retrieval were suggested. Standard hCG dose concomitant with GnRHa (dual trigger), 35–37 h before oocyte retrieval is offered to normal responders patients, resulting in improved oocyte/embryo quality and IVF outcome. GnRHa 40 h and standard hCG added 34 h prior to oocyte retrieval (double trigger), respectively are offered to patients demonstrating abnormal final follicular maturation despite normal response to COH. The double trigger results in significantly higher number of oocytes retrieved, higher proportions of the number of oocytes retrieved to the number of follicles >10 mm and >14 mm in diameter on day of hCG administration, higher number of MII oocytes and proportion of MII oocytes per number of oocytes retrieved, with the consequent significantly increased number of top-quality embryos, as compared to the hCG-only trigger cycles. Standard hCG dose concomitant with GnRHa (dual trigger), 34 h before oocyte retrieval should be offered to poor responders patients, aiming to overcome premature luteinization, while achieving high yield of mature oocytes. Further studies are required to support this new concept prior to its implementation as a universal COH protocol to IVF practice.